THE INFLUENCES OF IMPLEMENTING PROJECT-BASED LEARNING AND STUDENTS’ MOTIVATION IN IMPROVING WRITING SKILL - Vicxy Dilarose; Mulyadi; Hanni Yukamana (Esteem Journal of English Education Study Programme, 2025)
This study aims to examine the impact of implementing Project-Based Learning (PBL) and students' motivation on improving writing skills. The research adopts a factorial design method, incorporating both a control and an experimental group. The sample consists of two randomly selected classes, with one group applying the PBL method and the other serving as a control group without any specific instructional method. Data collection was conducted through writing tests and student motivation questionnaires. The analysis reveals a significant difference in students’ ability to write explanation texts between those taught using the PBL approach and those who did not receive structured instructional methods. Furthermore, students’ learning motivation positively influences their writing skills. Those with higher motivation demonstrated greater improvements in writing proficiency compared to students with lower motivation levels. Based on these findings, this study concludes that implementing Project-Based Learning can effectively enhance students’ writing skills, particularly in explanation texts, when accompanied by strong learning motivation. As a result, it is recommended that teachers incorporate the PBL method into writing instruction and actively foster student motivation to maximize learning outcomes.